2007
DOI: 10.1243/0954406jmes488
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study for the impact of liquid droplets on solid surfaces

Abstract: The impinging behaviour of liquid droplets on solid surfaces is studied using a computational approach. The analysis comprises the unsteady three-dimensional conservation equations of mass and momentum, with the surface tension effect treated by the continuous surface force model. Gas-liquid interfacial motions are simulated by the volume-of-fluid method in conjunction with the piecewise linear interface construction technique. In the computer code validation for a water droplet impacting on a polished stainle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Experiments with droplets of different Weber numbers were investigated for rectangular slots by Subramani et al 12 , where two splashing regimes were identified: one internal splash similar to impacts on planar surfaces and the other where the cavity structure causes a splash to extend outside of the cavity. Deposition into square cavities was investigated using a volume of fluid method by Yang et al 13 , including off-centre deposition, and it was found that the cavity did not fully fill for an off-centre deviation of 10 . Experiments and computational fluid dynamics (CFD) simulations of droplet deposition into cavities were performed by Liou et al 14 , where Weber number and cavity wall wettabilities were studied to find optimum wetting conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments with droplets of different Weber numbers were investigated for rectangular slots by Subramani et al 12 , where two splashing regimes were identified: one internal splash similar to impacts on planar surfaces and the other where the cavity structure causes a splash to extend outside of the cavity. Deposition into square cavities was investigated using a volume of fluid method by Yang et al 13 , including off-centre deposition, and it was found that the cavity did not fully fill for an off-centre deviation of 10 . Experiments and computational fluid dynamics (CFD) simulations of droplet deposition into cavities were performed by Liou et al 14 , where Weber number and cavity wall wettabilities were studied to find optimum wetting conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It leads to numerous applications in industry, such as printing and soldering [1][2][3]. Usually, it is studied by taking a liquid droplet atop a solid surface as an object [4], and the variables are related by Young equation (1) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%